Achieving high average power factor in tetrahedrite Cu12Sb4S13 via regulating electron-phonon coupling strength. (January 2022) - Yan, Yanci; Li, Nanhai; Wang, Guiwen; Xiong, Qihong; Fan, Lizhu; Jiang, Pengfei; Lu, Xu; Wang, Guoyu; Zhou, Xiaoyuan
Abstract: Lattice anharmonicity usually leads to low lattice thermal conductivity and thus is favored by thermoelectrics. However, if the anharmonicity is driven by strong lattice distortion, it is possible that the strong coupling between electrons and phonons would result in low carrier mobility. Yet, the fundamental physics of the competition between anharmonicity and mobility is not fully understood. In this study, taking thermoelectric tetrahedrite Cu12 Sb4 S13 as example, we try to elucidate such mechanism experimentally by analyzing electrical transport and local chemical bonding environment. It is found that substituting Sb with Sn can effectively suppress the local vibrational amplitude of Cu atoms, which is the origin of anharmonicity. As a result, electron-phonon coupling strength is regulated as well as the electrical conductivity and Seebeck coefficient are spontaneously promoted, leading to a substantially enhanced average power factor by more than 60%. Combined with the suppressed of electron-phonon coupling strength and exsolution process, a maximum zT of 1.1 at 723 K is achieved. These findings shed some light on the relationship between anharmonicity and carrier mobility, further emphasizing the importance of considering electron-phonon coupling for designing novel thermoelectric materials. Graphical abstract: In tetrahedrite Cu12 Sb4 S13, which holds strong lattice anharmonicity, substituting Sb with Sn can effectively tune electron-phonon coupling strength, resulting in a substantial average power factor enhancement by more than 60% with spontaneously enlarged electrical conductivity and Seebeck coefficient. Image 1 Highlights: The clarification of the long-lasting puzzle for the electrical transport mechanisms for tetrahedrites. The demonstration for the intimate relationship between lattice anharmonicity and mobility in tetrahedrites. The manipulation of electron-phonon coupling strength that results in a great enhancement of 60% in average power factor.